1997
DOI: 10.1177/00220345970760100601
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Smoking Cessation, and Tooth Loss

Abstract: Smoking is associated with an increased risk of tooth loss, but it is not known if this risk decreases significantly when individuals quit smoking. The objectives of this study were to describe the rates of tooth loss by smoking status in two populations of medically healthy men and women. Among the men, rates of tooth loss and edentulism in relation to smoking cessation were also evaluated. The subjects were drawn from a group of 584 women (aged 40 to 70) recruited from the Boston, MA, area and a separate pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
112
2
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 32 publications
18
112
2
13
Order By: Relevance
“…9 In the United States, an association between smoking and tooth loss has been identified. 6,[10][11][12][13][14][15][16] Such an association was also found in subjects residing in Sweden, [17][18][19] Australia, 20 Iceland, 21 Jordan, 22 Brazil, 23 and Kuwait. 24 In South-East Asian countries, only a few studies have reported on the association between smoking and tooth loss.…”
Section: Methodsmentioning
confidence: 78%
“…9 In the United States, an association between smoking and tooth loss has been identified. 6,[10][11][12][13][14][15][16] Such an association was also found in subjects residing in Sweden, [17][18][19] Australia, 20 Iceland, 21 Jordan, 22 Brazil, 23 and Kuwait. 24 In South-East Asian countries, only a few studies have reported on the association between smoking and tooth loss.…”
Section: Methodsmentioning
confidence: 78%
“…This movement alters the relationship between different parts of the face (August and Kaban, 1999). While a common aspect of the aging process, cultural factors such as poor diet and smoking increase the risk of tooth loss at all ages (Krall et al, 1997). Socioeconomic disparities in edentulism prevalence also exist (Cunha-Cruz et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…3,[26][27][28][29][30][31][32][33][34][35][36] Moreover, smokers suffer a greater rate of tooth loss than non-smokers. [37][38][39][40][41][42] Tooth loss can, indeed, be the result of other circumstances than periodontal disease. However, when the confounding effects of other factors, such as caries, have been controlled for, it becomes evident that excess tooth loss in the average smoker is associated with the periodontal destruction.…”
Section: Smoking and Periodontal Inflammationmentioning
confidence: 99%
“…Results are currently available from a limited number of cohort studies where smokers and nonsmokers have been compared with reference to the prevalence or severity of periodontal disease. [20][21][22]36,40,41,[43][44][45]49,50 All of these unanimously indicate that periodontal disease more frequently affects and is more severe in smokers than in non-smokers. Intriguingly, studies including former smokers who have given up smoking in the past conclude that former smokers are less frequently affected than smokers or that they exhibit less severe disease.…”
Section: Smoking and Periodontal Inflammationmentioning
confidence: 99%